Efficacy of Sodium-Glucose Cotransporter 2 Inhibitors in Patients With Concurrent Type 2 Diabetes Mellitus and Non-Alcoholic Steatohepatitis: A Review of the Evidence - Yabiku, Koichi (Frontiers in Endocrinology, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide, and 14 more than half of individuals diagnosed with type 2 diabetes concurrently present with NAFLD. 15 There is a bidirectional pathological relationship between the two conditions, whereby NAFLD 16 increases the risk of type 2 diabetes, and type 2 diabetes contributes to and accelerates the 17 progression of NAFLD. Furthermore, over 30% of patients with NAFLD progress to non-18 alcoholic liver steatohepatitis (NASH), which then increases the risk of cirrhosis and 19 hepatocellular carcinoma. Despite its high prevalence and the potential clinical implications, the 20 underlying pathogenesis of NAFLD has yet to be fully elucidated, and there is no consensus 21 regarding standard diagnosis and treatment for either NALFD or NASH. As patients with both 22 NASH and type 2 diabetes have impaired hepatic function owing to chronic inflammation and 23 the resulting structural changes caused by hepatic fat accumulation, they face reduced options for 24 antidiabetic treatment. SGLT-2 inhibitors inhibit glucose reabsorption in the proximal tubule, 25 with increased excretion of glucose in urine and decreased glucose levels in plasma, and their 26 glycemia-lowering effect is insulin-independent. Several other beneficial effects have been 27 reported for SGLT-2 inhibitors, including reduced risks of cardiovascular and renal diseases, 28 improved blood pressure control, body weight reduction, and reductions in liver fat content. 29 Experimental studies in mouse models have suggested that SGLT-2 inhibitors may have 30 beneficial modulatory effects on NAFLD/NASH. Several trials in patients with type 2 diabetes 31 have also suggested that these drugs may be useful in treating both type 2 diabetes and NAFLD 32 or NASH. However, further research is needed to identify the mechanisms by which SGLT-2 33 inhibitors affect fatty liver and steatohepatitis. In this state-of-the-art review, we explore the 34 literature on the efficacy of SGLT-2 inhibitors in patients with type 2 diabetes and NASH, and 35 present arguments for and against the use of SGLT-2 inhibitors in this patient population.